The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/met10121564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ion-Diffusion Solid-Phase Reduction of Iron Oxides of Technogenic Origin in the Presence of the Liquid Phase and without it

Abstract: The processes of iron oxides’ reduction have a complex physicochemical mechanism, with the participation of solid, liquid, and gaseous substances. The article discusses the existing models for the reduction of iron oxides and provides data on the thermodynamic possibility of carrying out the reactions of their reduction through the solid and gas phases. Experimental data on the reduction of iron from industrial scale, obtained by the DSC (differential scanning calorimetry) method, show the kinetic dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…This cementite reacts with carbon dioxide (generated in step I) following Eq. ( 5) [10]. In this step, fewer gases than in the previous step would be formed, which is reflected in a lesser mass loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cementite reacts with carbon dioxide (generated in step I) following Eq. ( 5) [10]. In this step, fewer gases than in the previous step would be formed, which is reflected in a lesser mass loss.…”
Section: Resultsmentioning
confidence: 99%
“…This process is accompanied with gasification of carbon via the Boudouard reaction which promotes the sudden mass loss through Eq. ( 3) [4,10]. This reaction controls the overall process of the reduction.…”
Section: Calculation Of the Gibbs Free Energymentioning
confidence: 99%
“…It is established that the reduction proceeds in the sequence Fe 3 O 4 -FeO-Fe 3 C-α-Fe. In [ 5 ], the MCA influence (the briquetting pressure of the initial reagents) on the reduction in kinetics of scale of iron oxides during heating is considered. It was found that the reduction of iron oxides in scale proceeds in a solid-phase manner in three modes: diffusion-free, intermediate and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 5 ], only one of the MCA methods was considered (pressing). However, preliminary grinding is important for scale secondary processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation